Strategi Pemasaran Pasar Payungi Dalam Membangun Image Sebagai Pasar Kreatif Di Kota Metro - Nina Lelawati; Nani Septiana; M Farid Algiffari (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to find out and describe what marketing strategies are used by the umbrellamarket in building an image as a creative market in Metro City, whether they are the same asprevious research or not. Based on the results of the research and discussion that has beencarried out, the creation of the umbrella market image as a creative market in Metro city isdetermined by the marketing strategy and procedures for building a positive image in thecommunity, the marketing strategy carried out by the umbrella market is almost entirelythrough social media, relations with the community , Sales Promotion, Events andExperience as well as Direct Selling or direct sales, this is of course supported by thecharacter of the umbrella market and also interesting things that can be highlighted in theumbrella market so that the umbrella market can be said to be a Creative market in MetroCity